Urban Traffic Flow Optimization Algorithm - Ullah, Wasif (International Journal of Scientific World, 2026)
Swarm intelligence algorithms inspired by natural and artificial systems have demonstrated strong capability in solving complex optimiza-‎tion problems. This study proposes a novel population-based metaheuristic, termed the Urban Traffic Flow Optimization Algorithm ‎‎(UTFOA), which is inspired by adaptive decision making and self-organized traffic dynamics observed in modern urban environments. In ‎the proposed framework, each search agent is modeled as an autonomous driver navigating toward an optimal route under dynamically ‎evolving traffic conditions. The algorithm captures three fundamental traffic behaviors, namely route exploration, adaptive following, and ‎congestion avoidance, and formulates them as mathematical operators that jointly balance global exploration and local exploitation. In addition, traffic pressure and driver experience mechanisms are incorporated to regulate adaptive behavior throughout the iterative search process. ‎Theoretical analysis indicates that the proposed algorithm preserves population diversity, satisfies global convergence conditions under ‎Markov chain theory, and exhibits controllable computational complexity. The proposed model introduces a human-inspired perspective for ‎designing adaptive optimization algorithms‎.
Keywords: Swarm Intelligence; Metaheuristic Optimization; Traffic Flow Dynamics; Adaptive Search; Driver Behavior Modeling